2012
DOI: 10.2298/sarh1212746d
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic exercise in the treatment of children with cerebral palsy

Abstract: Aquatic exercise program can be useful in improving gross motor functioning, reducing spasticity and increasing cardiorespiratory endurance in children with spastic CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
3
8
0
3
Order By: Relevance
“…[3][4][5][6][7][8] However, muscle weakness, poor joint alignment, and muscle contracture in children with cerebral palsy leads to pain and fatigue, causing problems in engagement and compliance in conventional land-based therapy. [9][10][11] Aquatic therapy protects joint integrity more than land-based exercises 12 and has proved useful in improving gross motor function, 3,4 reducing spasticity, increasing cardiorespiratory endurance 13,14 and vital capacity, and improving gait in children with cerebral palsy. 3,8 In children diagnosed with cerebral palsy at Gross Motor Functional Classification System Levels IV and V, landbased activities are more difficult than for those at Gross Motor Functional Classification System Levels I and II.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] However, muscle weakness, poor joint alignment, and muscle contracture in children with cerebral palsy leads to pain and fatigue, causing problems in engagement and compliance in conventional land-based therapy. [9][10][11] Aquatic therapy protects joint integrity more than land-based exercises 12 and has proved useful in improving gross motor function, 3,4 reducing spasticity, increasing cardiorespiratory endurance 13,14 and vital capacity, and improving gait in children with cerebral palsy. 3,8 In children diagnosed with cerebral palsy at Gross Motor Functional Classification System Levels IV and V, landbased activities are more difficult than for those at Gross Motor Functional Classification System Levels I and II.…”
mentioning
confidence: 99%
“…In addition, warm water can decrease muscle tension, muscle spasm, and relieve muscle tension, which can promote a more effective way to exercise. Also, increased muscle strength can be expected by increasing the speed of movement in the opposite direction fo the flow of water [12]. The results of this study showed that after intervention, the trunk control scale was significantly higher in static balance, dynamic balance, and dynamic reach, and variability in weight distribution was significantly lower compared to before intervention.…”
Section: Discussionmentioning
confidence: 65%
“…They found neurodevelopmental treatment (NDT), functional and task-oriented training, and therapeutic horse riding or hippotherapy had Level IV evidence, hinting at the causality of reduction in spasticity. Dimitrijevi c and colleagues 16 found a statistically significant reduction in spasticity in children with CP who participated in a twiceweekly aquatic therapy program for 12 weeks. Constraint-induced movement therapy (CIMT) may show functional benefits, but does not statistically change upper limb spasticity.…”
Section: Physical Management Of Hypertonicitymentioning
confidence: 98%